Prevalence, bacterial profile, antimicrobial resistance pattern, and predictors of blood culture positive sepsis among adults admitted at Jinja Regional Referral Hospital in Uganda - Kara, Naqeeb; Peris, Alina; Abonga, Charles; Muyinda, Asad; Muhumuza, Joshua; Akaba, Kingsley; Abdi, Awil; Nur, Ibrahim; Vidya, Sankarapandian; Okumu, Mitchel (Frontiers in Tropical Diseases, 2025)
IntroductionThere is paucity of data on the prevalence, bacterial profile, antimicrobial resistance (AMR) pattern, and predictors of blood culture positive sepsis among adults admitted at Jinja Regional Referral Hospital (JRRH). The aim of the present study was to determine the prevalence, bacterial profile, AMR pattern, and predictors of blood culture positive sepsis among adults admitted at JRRH.MethodsThis was a cross-sectional study between June and August 2023 where patients were recruited using the quick Sepsis Related Organ Failure Assessment (qSOFA) criteria. Data (Sociodemographic and clinical), and blood was collected from eligible patients. Blood was incubated, sub-cultured, and their antimicrobial susceptibility was determined using the disc diffusion method. Data was analyzed on the statistical package for the social sciences (SPSS version 26) and summarized using descriptive statistics and logistic regression.ResultsMost patients were male (132/261, 50.6%), aged 18-36 (155/261, 71.6%), single (146/261, 55.9%), Christian (224/261, 85.8%), had secondary level of education (129/261, 49.4%), were students (93/261, 35.6%), and consumed alcohol (35/261, 13.4%). The prevalence of blood culture-positive sepsis was 53 out of 261 (20.32%), the most isolated pathogens were Staphylococcus aureus (20.8%, 11/53), Streptococcus spp. (18.9%, 10/53), and Klebsiella pneumoniae (13.2%, 7/53). S. aureus exhibited 100% resistance to gentamicin, tetracycline, and minocycline. Streptococci spp was resistant to tetracycline, while K. pneumoniae was resistant to gentamicin. Blood culture positive sepsis was associated with the duration of symptoms for>5 days (aOR=2.010, CI=1.602-6.705, p=0.026), central nervous system (CNS) symptoms (aOR=3.058, CI=1.365-6.849, p=0.007), and low peripheral oxygen saturation (aOR=3.837, CI=1.733-8.496, p=0.001).ConclusionThe findings suggest that blood culture positive sepsis occurred most frequently among male patients, with most patients aged 18–36 years, though further analysis is needed to establish strong demographic associations. The findings highlight notable antimicrobial resistance in Staphylococcus aureus, Streptococcus spp., and Klebsiella pneumoniae, which should prompt further investigation into antimicrobial stewardship programs. Furthermore, prolonged symptom manifestation, CNS involvement, and hypoxemia seem to be key predictors of blood culture positive sepsis in the study area. Public health interventions in the study area should focus on improving early detection and management of sepsis, with a particular emphasis on promoting awareness in high-risk groups.